From Weaving Schemes to Weaving Patterns - Kollár, Ján (INFOCOMP Journal of Computer Science, 2006)
Coming out from the process functional paradigm and using PFL – a process functional language, a generalized approach to weaving at the micro-structural level is presented. Exploiting the application of processes and PFL reflection property, we develop a generalized weaving scheme and we express it in the form of weaving pattern. Different specializations and extensions of weaving patterns occurring in aspect oriented languages are discussed. Weaving patterns expressed in terms of weaving chains provide us with the flexibility inevitable for the aspect oriented evolution of software systems instead of aspect oriented programming. Presented abstraction in the form of patterns comes out from integrating imperative, purely functional and object paradigms in the process functional paradigm and it may contribute to the application of aspect oriented approach to the area of automatic evolution of software systems.